Location in a disk city with consumer concentration around the center - Manfred Stadler (University of Tübingen, Faculty of Economics and Social Sciences, 2018)
The paper studies a two-stage location-price duopoly game in a disk city with consumer concentration around the city center. When consumers are uniformly distributed over the plane, unconstrained firms locate outside of the city. Consumer concentration, however, induces firms to locate nearer to each other and, when the degree of concentration is sufficiently high, inside of the city. Prices and firm profits decrease in the degree of consumer concentration. We explicitly solve the model for classes of cone-shaped, dome-shaped, and bell-shaped consumer densities. In all cases we identify a loss of welfare due to the strategic effect which causes the firms' spatial differentiation being too large.
urn:nbn:de:bsz:21-dspace-850704
Keywords: C72; L13; R32; 330; location strategies; disk city; concentration of consumer demand